👤

Seja f(x) e g(x), funções cujas leis de formação são, respectivamente, f(x) = 2x -5 e g(x) = -x + 2, podemos afirmar que o valor de f(g(2)) – g(-3) é igual a: *
7 pontos
A) 0
B) 5
C) -5
D) -10
E) -12


Resposta :

Resposta:

f(g(2)) = f(-2+2)=f(0)=-5

g(-3)=-(-3)+2=5

f(g(2)) – g(-3)  =-5-5 =-10

Letra D

[tex]i)[/tex]

[tex]f(x) = 2x - 5 \\ g(x) = - x + 2[/tex]

[tex] \therefore[/tex]

[tex]g(2) = - 2 + 2 = 0[/tex]

[tex]g( - 3) = 3 + 2 = 5[/tex]

[tex]ii) \: f(0) + 5 \\ = - 5 - 5 = -10[/tex]

[tex] \therefore[/tex]

[tex] \boxed{f(g(2)) - g( - 3) = -10}[/tex]